LABOUR MARKET REQUIREMENTS FOR FOREIGN LANGUAGE EDUCATION WITH A FOCUS ON SPANISH - Mária Spišiaková; Zuzana Kittová (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
The paper focuses on education in the field of foreign languages, particularly Spanish, in the framework of university study of economic and managerial orientation in Slovakia in order to find out what the labour market requirements are for graduates in the field of foreign language skills. In our research, we focus on Spanish, as no similar relevant research has been done to date in this foreign language. Current research shows that the graduates of economics and management fields lack the link between the content of education and the requirements of the labour market, as well as preparation in the field of foreign language skills. This calls for a better understanding of the real needs of employers and graduates. This paper is based on a questionnaire survey among potential employers of graduates of the University of Economics in Bratislava who require foreign language skills, mainly Spanish, as well as of graduates of the University of Economics in Bratislava who use foreign languages, in particular Spanish in their employment. The paper provides an overview of the specific language competencies and knowledge that are needed in the labour market. The ambition of research is to contribute to improving the link between higher education content and the real needs of the labour market, and thus to boosting  the employability of graduates in the labour market.